ANALYSIS OF THE INHIBITORY POTENTIAL OF STREPTOCOCCUS SALIVARIUS ISOLATED FROM ADULT SALIVA AND THE TONGUE DORSUM FOR THE GROWTH OF CANDIDA ALBICANS - Fairiska, Nindy; Bachtiar, Boy M; Gultom, Ferry P (International Journal of Applied Pharmaceutics, 2017)
Objectives: The objective of this study is to analyze the effectiveness of Streptococcus salivarius and its protein for inhibiting the growth of Candida albicans. Methods: The analysis was conducted using polymerase chain reaction, sodium dodecyl sulfate polyacrylamide gel electrophoresis, a Bradford test, deferred antagonism test, and well-diffusion agar. Result: S. salivarius, isolated from saliva and the tongue dorsum, and its protein do not inhibit the growth of C. albicans. The morphology of C. albicans did not change after being exposed to protein produced by S. salivarius. Conclusions: S. salivarius and its protein do not inhibit the growth of C. albicans. However, the bacterium has the capacity to maintain fungus morphology in the form of blastospora.